Moc apotropaionu. Nie tylko o starożytnych reminiscencjach w średniowiecznym uzbrojeniu z ziem polskich = The power of apotropaion. On ancient reminiscences in medieval weaponry from Polish lands and more - Michalak, Arkadiusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Shield surfaces have been decorated since ancient times. Often repeated motifs included images of evil eyes, monsters, or mythical animals (signa horribilia) (Fig. 1). Depictions on shields were apotropaic - they increased its protective properties. Popular face motifs that also appeared on the shields at that time were lion emblems; figures with stylized animal ears, which evoked an association with the figure of a mythological satire; and the personification of celestial bodies: the Sun and the Moon.
Keywords: tarcza; apotropaion; gorgoneion; uzbrojenie; antyczne inspiracje; średniowiecze; okres wczesnonowożytny; shield; arms and armour; Middle Ages; early modern period